Delivering tertiary centre specialty care to ALS patients via telemedicine: a retrospective cohort analysis. Issue 5 (3rd July 2017) - Selkirk, Stephen M.; Washington, Monique O.; McClellan, Frances; Flynn, Broderick; Seton, Jacinta M.; Strozewski, Richard
Abstract: Objective: This study was undertaken to determine if ALS patients evaluated via telemedicine received the same quality of care as patients evaluated by traditional face-to-face encounters. Methods: A retrospective cohort study design was used. Participants were patients diagnosed with ALS that received multidisciplinary care at the tertiary Cleveland VA ALS Centre between 1 March 2008- and 31 anuary 2015. Participants were not randomised, but chose telemedicine based on preference, disability level or distance from the clinic. Telemedicine in this study consisted of a video conferencing platform enabling remote rather than face-to-face encounters with participants. Results: There was no significant association between receiving quality ALS care and the mode of care. There was a trend for telemedicine patients to utilise home health care less often than those that received clinic care (AOR 0.50; 95% CI 0.16–1.59). There was no significant difference in survival time between the two groups (log-rank test χ 2 = 3.62, df = 1, p = 0.05). Patients receiving telemedicine had a higher probability of remaining stable or having <30% decrease in ALSFRS-R over time (log-rank test χ 2 = 4.46, df = 1, p = 0.03). There was a significantly lower risk of disease progression for patients receiving telemedicine (HR = 0.39, 95% CI = 0.16–0.93). Conclusions : Patients managed by telemedicine received the same quality of care and had similar outcomes to those patients seen via traditional face-to-face encounters. Telemedicine is an effective platform for delivering high quality tertiary ALS care.